2020
DOI: 10.7717/peerj.9751
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncratic liver pigment alterations of five frog species in response to contrasting land use patterns in the Brazilian Cerrado

Abstract: Background Changes in land use trigger environmental changes that can lead to decreased biodiversity and species loss. The liver is an essential detoxification organ that reflects systemic physiological responses to environmental changes. Here, we tested whether contrasting land use patterns influence the amount of substances from the hepatic cellular catabolism and melanomacrophages (MMs) of five anuran species in the Brazilian Cerrado. Methods We collected the same five species of pond-dwelling frogs in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
1
6
0
1
Order By: Relevance
“…Moreover, the results obtained in this work show that at 96 h there is a signi cant decrease in the area of the pigments melanin and hemosiderin in the hepatic MMC. According to previous studies, the decrease in these pigments is related with a reduction in phagocytic and protective activity against oxidizing agents of MMC in the liver (Fenoglio et al, 2005;Pérez-Iglesias et al, 2016;Fanali et al, 2018;Franco-Belussi et al, 2020). Focusing on the response of the catabolic pigment hemosiderin in S1, this work again reports similar results to those previously described for us in this species after herbicide exposure (Pérez-Iglesias et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the results obtained in this work show that at 96 h there is a signi cant decrease in the area of the pigments melanin and hemosiderin in the hepatic MMC. According to previous studies, the decrease in these pigments is related with a reduction in phagocytic and protective activity against oxidizing agents of MMC in the liver (Fenoglio et al, 2005;Pérez-Iglesias et al, 2016;Fanali et al, 2018;Franco-Belussi et al, 2020). Focusing on the response of the catabolic pigment hemosiderin in S1, this work again reports similar results to those previously described for us in this species after herbicide exposure (Pérez-Iglesias et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…For instance, a study on endemic bird species distribution in Mexico showed that land‐use modifications converted natural habitats into other land‐use classes such as agricultural, industrial and urban, thereby threatening endemic species persistence (Almazán‐Núñez et al, 2018). Similarly, Franco‐Belussi et al (2020) observed that more natural habitats are being replaced by agricultural areas and settlements (urbanisation), leading to decreased amphibian populations and genomic diversity. In addition, a study on amphibians in Asia showed that forest loss degradation and fragmentation as a result of high deforestation rates have impacted the presence, abundance, diversity and variability of amphibians (Karraker et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in land‐use and land‐cover (LULCC) contribute to the extinction of endemic, rare and endangered biodiversity species such as KST. LULCC is aided by human activities such as infrastructure development and agriculture, which threaten species through habitat loss, fragmentation and destruction (Doe et al, 2022; Franco‐Belussi et al, 2020; Mmbaga et al, 2017; Ngongolo et al, 2020; Ngongolo & Mtoka, 2013; Sigala et al, 2022). It has also been reported that human‐induced LULCC triggers ecological changes that lead to a decrease in biodiversity and increased species loss (Franco‐Belussi et al, 2020; Rija et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Land use land cover changes (LULCC) contribute to the extreme loss and extinction of endemic, rare and endangered biodiversity species such as the Kihansi spray toads (KST). Human activities such as infrastructure development and agriculture support LULCC and threaten species through habitat loss, fragmentation, and destruction (Mmbaga et al, 2017;Franco-Belussi, et al, 2020). It has also been reported that human induced LULCC triggers ecological changes that lead to a decrease in biodiversity and increased species loss (Franco-Belussi, et al, 2020;Rija et al, 2011).…”
Section: Introductionmentioning
confidence: 99%